Comparative Study of The Absorption of Active Zeolite and Ethylenedimintetraacetate (EDTA) Modified Zeolite as Absorbent in a Mixture of Copper (II), Nickel (II), and Zinc (II) Ions - Agusnar, Harry (Journal of Chemical Natural Resources, 2020)
Research about the absorption of activated zeolite and EDTA-modified zeolite has been successfully conducted to absorb Cu2+, Ni2+, and Zn2+ ions. Natural zeolite used from Sarulla, Pahae Jae, North Sumatera. This research aims to determine the effect of activated zeolite and EDTA-modified zeolite to absorb Cu2+, Ni2+, and Zn2+ ions in the mixture. In this research, natural zeolite was sifted with a 120 mesh sieve, then calcinated at 300ÂºC, and activated with HCl 15%. The natural zeolite was modified with EDTA 0,1 M that was applied as an absorbent on Cu2+, Ni2+, and Zn2+ ions which each of the initial concentrations was 50 mg/L with variations of contact time were 1, 2, and 3 hours and weight of adsorbent were 0,25 g/25 mL, 0,5 g/25 mL, and 1 g/25 mL and also the determination of metal concentration was used ICP-OES method. The results obtained showed that EDTA-modified zeolite and activated zeolite were able to decrease the concentration of metal, but the absorption ability of EDTA-modified zeolite was bigger than activated zeolite. The result of the absorption experiment of Cu2+, Ni2+, and Zn2+ ions showed that the best absorption has been carried out with a contact time was 3 hours and the weight of absorbent was 1 g/25 mL. The percentages of decrease in this research by adding activated zeolite as an absorbent on Cu2+, Ni2+, and Zn2+ ions were 95.99.77.92, and 81,62%, respectively. In addition, the percentages of decreasing by adding EDTA-modified zeolite as an absorbent Cu2+, Ni2+, and Zn2+ ions were 98.79, 96.07, and 97,54%, respectively.